Hearing Outcomes in Conservatively Managed Vestibular Schwannoma Patients With Serviceable Hearing. Issue 8 (September 2018) - Hunter, Jacob B.; Dowling, Eric M.; Lohse, Christine M.; O'Connell, Brendan P.; Tombers, Nicole M.; Lees, Katherine A.; Thompson, Reid S.; Haynes, David S.; Carlson, Matthew L.
Abstract : Objective: To characterize the risk of progression to nonserviceable hearing in patients with sporadic vestibular schwannomas (VS) who elect initial observation. Study Design: Retrospective case series. Setting: Two tertiary care centers. Patients: VS patients with serviceable hearing who underwent at least two audiograms and two MRI studies before intervention or loss to follow-up. Main outcome measure(s): Serviceable hearing, defined as the pure tone average ⩽ 50 dB HL and word recognition score ≥ 50%. Results: Four-hundred sixty-six patients (median age of 57 yr and median tumor diameter of 7.3 mm) had serviceable hearing at presentation and were followed for a median of 2.3 years (IQR 1.0 – 4.0). Kaplan–Meier estimated rates of maintaining serviceable hearing (95% CI; number still at risk) at 1, 3, 5, 7, and 10 years following diagnosis were 94% (91–96; 357), 77% (73–82; 172), 66% (60–73; 81), 56% (49–65; 31), and 44% (33–59; 10), respectively. Each 10-dB increase in pure-tone averages at diagnosis was associated with a 2-fold increased likelihood of developing nonserviceable hearing (hazard ratio 2.07; p  < 0.001). Each 10% decrease in word recognition score was associated with a 1.5-fold increased likelihood of developing nonserviceable hearing (hazard ratio 1.48; p  < 0.001). Conclusions: Among patients with sporadic VS, good baseline word recognition score and low pure-tone average are jointly associated with maintenance of serviceable hearing. These data may be used to guide patient counseling and optimize management.